Aplikasi Game Flatfrom Art Lewat Construct 2 Dengan Menggunakan Metode Quadtree - Simamora, Lita Martauli; Mesran, Mesran (STMIK Budi Darma, 2020)
The use of media as a learning tool is appropriate and interesting in the introduction of traffic signs to increase knowledge. Traffic game application is a media that is run on an android smartphone as a means to recognize and learn the types of traffic signs. The research method in designing a traffic sign game is Quad-Tree which collision collision / collision of two different objects in the game area by dividing the arena of the same size game if there are two or more objects in the same area so divide the area again into four equal sized parts until no objects are in the same area. Providing interesting knowledge and while playing to the community, a traffic game application is designed to provide knowledge of road equipment containing symbols, letters, numbers, sentences or a combination of them, which are used to provide warnings, prohibitions, commands and instructions in the past educational games cross.